Arts and Crafts: Fun Activities to Train Early Childhood Cooperation - Idzni Azhima (Department of Early childhood Education, 2019)
Abstract : Cooperation is one form of an aspect of social emotional development that needs to be developed in early childhood to be able to have a collaborative attitude, interact with other people and have an attitude of responsibility for their work. Learning methods that can be used in an effort to improve the ability of child cooperation, namely by group work methods. In this study, group work was applied based on playing art and craft activities. The purpose of writing this article is to add an alternative method of learning to improve collaboration skills in early childhood.